2002
DOI: 10.1177/1523422302043004
|View full text |Cite
|
Sign up to set email alerts
|

Grounded Theory Research and Theory Building

Abstract: The problem and the solution. A challenging mandate recently advanced by human resource development (HRD) scholars and practitioners has been the development of theory with clear implications for practice. The grounded theory research approach presents promising possibilities for the development of theoretical frameworks that emerge from research situated in practice and enhance the HRD theorist-HRD practitioner partnership in the process of theory building.The objective of this chapter is to outline the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
0
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 16 publications
0
77
0
9
Order By: Relevance
“…Matavire and Brown [36] identified the main principles of grounded theory as emergence, constant comparative analysis and theoretical sampling. Grounded theory methodology was chosen in this study for its comparative process that identifies relationships between categories, and for the fact that it is known to be a flexible method that allows researchers to be innovative [38]. These properties make it a suitable choice for gaining a fresh perspective on the factors that significantly affect customer e-service adoption.…”
Section: Research Approach: Grounded Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Matavire and Brown [36] identified the main principles of grounded theory as emergence, constant comparative analysis and theoretical sampling. Grounded theory methodology was chosen in this study for its comparative process that identifies relationships between categories, and for the fact that it is known to be a flexible method that allows researchers to be innovative [38]. These properties make it a suitable choice for gaining a fresh perspective on the factors that significantly affect customer e-service adoption.…”
Section: Research Approach: Grounded Theorymentioning
confidence: 99%
“…The grounded theory research approach is suitable for the development of theoretical frameworks as the methodology possesses the following characteristics [38]: responsiveness aimed at conceptual values and not just the values of the investigator; the ability to fit the situation being researched; and the formation of rigorous theory that emerges from a thorough analysis of contextual data [55]. Grounded theory, in interpretative information systems research, is described as traceable to the data and as 'fluid', which means that the emphasis is on the process and the temporal nature of the theory [37].…”
Section: Grounded Theory: Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The research conducted on religious identities and purchase patterns reported that people affiliated with different religious identities purchase accordingly and their shopping patterns are a reflection of their religious identity [43] . Religion as a belief pattern according to which the followers of that religion respond [19] . The relation between the Islamic faith and consumption pattern and reported a positive significant relationship [20] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such products are considered to be the safety benchmark and high in quality [17] . The influence of the values moral and religious are not only related to just high involvement products but also to comparatively less involvement field like packaged and natural food [19] . The growing trend of non-Muslim consumers in the Halaal food products has been investigated by several researchers [47] [35] .…”
Section: Literature Reviewmentioning
confidence: 99%